2010
DOI: 10.1095/biolreprod.110.084277
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Fibroblast Growth Factor 18 in the Ovarian Follicle in Cattle1

Abstract: Fibroblast growth factors (FGF) are involved in paracrine signaling between cell types in the ovarian follicle. FGF8, for example, is secreted by oocytes and controls cumulus cell metabolism. The closely related FGF18 is also expressed in oocytes in mice. The objective of this study was to assess the potential role of FGF18 in follicle growth in a monovulatory species, the cow. Messenger RNA encoding FGF18 was detected primarily in theca cells, and in contrast to the mouse, FGF18 was not detected in bovine ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 66 publications
8
62
1
Order By: Relevance
“…Unlike the known actions of other FGFs in the ovary, however, FGF18 appears to be a proapoptotic factor. Abundance of FGF18 mRNA and protein is higher in atretic compared with growing bovine follicles, and addition of FGF18 increased the amount of DNA laddering and caspase-3 activation in granulosa cells in vitro (Portela et al 2010(Portela et al , 2015. The mechanisms of action of FGF18 in the follicle have not been fully elucidated, but it may act through a murine double minute 2 (MDM2) and p53 upregulated modulator of apoptosis (PUMA, also known as BBC3) pathway (Portela et al 2015), although it has not yet been shown whether FGF18 alters p53 signaling.…”
Section: The Role Of the Fgf8 Family In Follicle Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Unlike the known actions of other FGFs in the ovary, however, FGF18 appears to be a proapoptotic factor. Abundance of FGF18 mRNA and protein is higher in atretic compared with growing bovine follicles, and addition of FGF18 increased the amount of DNA laddering and caspase-3 activation in granulosa cells in vitro (Portela et al 2010(Portela et al , 2015. The mechanisms of action of FGF18 in the follicle have not been fully elucidated, but it may act through a murine double minute 2 (MDM2) and p53 upregulated modulator of apoptosis (PUMA, also known as BBC3) pathway (Portela et al 2015), although it has not yet been shown whether FGF18 alters p53 signaling.…”
Section: The Role Of the Fgf8 Family In Follicle Developmentmentioning
confidence: 94%
“…Messenger RNA was not readily detected in the oocyte of cattle but is abundant in theca cells (Portela et al 2010). Addition of recombinant FGF18 to bovine granulosa cells in vitro inhibited oestradiol and progesterone secretion, and lowered abundance of mRNA encoding major estrogenic and progestagenic enzymes (Portela et al 2010).…”
Section: The Role Of the Fgf8 Family In Follicle Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…FGF2 is a candidate gene for fertility in cattle (Oikonomou et al 2011) and has been implicated in ovarian function (Portela et al 2010), embryonic development (Jackson et al 1997), and mortality (Khatib et al 2010). FGF2 is also known as mitogen, morphogen, and angiogenic factor (Michael et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The FGFs modulates a wide variety of ovarian function including proliferation, differentiation, steroidogenesis and apoptosis of GC in many farm animal species including human suggesting their role in regulation of ovarian folliculogenesis (Lavranos et al, 1994;Vernon and Spicer, 1994;Parrott and Skinner, 1997;Roberts and Ellis, 1999;Berisha et al, 2004;Buratini et al, 2007;Matos et al, 2007;Machado et al, 2009;Portela et al, 2010).…”
Section: Introductionmentioning
confidence: 99%